Filamentous cyanobacteria preserved in masses of fungal hyphae from the Triassic of Antarctica - Harper, Carla (My University, 2020)
Permineralized peat from the central Transantarctic Mountains of Antarctica has provided a wealth of information on plant and fungal diversity in Middle Triassic high-latitude forest paleoecosystems; however, there are no reports as yet of algae or cyanobacteria. The first record of a fossil filamentous cyanobacterium in this peat consists of wide, uniseriate trichomes composed of discoid cells up to 25 μm wide, and enveloped in a distinct sheath. Filament morphology, structurally preserved by permineralization and mineral replacement, corresponds to the fossil genus Palaeo- lyngbya, a predominantly Precambrian equivalent of the extant Lyngbya sensu lato (Oscillatoriaceae, Oscillatoriales). Specimens occur exclusively in masses of interwoven hyphae produced by the fungus Endochaetophora antarctica, suggesting that a special micro-environmental setting was required to preserve the filaments. Whether some form of symbiotic relationship existed between the fungus and cyanobacterium remains unknown.
PUBLISHED
Keywords: Microbiology; Mycology; Paleontology; Endochaetophora antarctica; Fungal reproduction; Lichen; Mesozoic; Mucoromycota; Oscillatoriaceae; Palaeolyngbya; Peat; Symbiosis; Smart & Sustainable Planet